2005
DOI: 10.1007/s00429-005-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

The morphogenesis of the exstrophy-epispadias complex: a new concept based on observations made in early embryonic cases of cloacal exstrophy

Abstract: Besides the presence of an abnormal opening into the cloaca, all embryos were characterised by an abnormal broadening of the caudal trunk at the level of the leg buds, which, in the youngest embryos, was associated with the abnormal presence of large aneurysmatic swellings of the dorsal aortae at this side. We postulate that these aneurysmatic swellings might be the primary defects leading to the development of EEC malformations. These space-occupying anomalies seem to cause abnormal distensions of the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It has been suggested that the cloaca/urogenital sinus and adjacent tissues differentiate into the urogenital and reproductive organs, including the urinary bladder (hereafter described as the bladder) in both sexes. This is supported by reports of complex congenital malformations such as: exstrophy-epispadias complex (exstrophy of cloaca or bladder and abnormal dorsal external genitalia; hereafter, dorsal external genitalia represents upper external genitalia); defective body wall, bladder and genitalia formation; and limb body wall defects that are probably caused by abnormalities in early development of the cloaca and urogenital sinus (Craven et al, 1997;Manner and Kluth, 2005;Penington and Hutson, 2003). The constellation of defects reported in affected individuals suggests that coordinated developmental programs regulate bladder and external genital morphogenesis.…”
Section: Introductionmentioning
confidence: 71%
“…It has been suggested that the cloaca/urogenital sinus and adjacent tissues differentiate into the urogenital and reproductive organs, including the urinary bladder (hereafter described as the bladder) in both sexes. This is supported by reports of complex congenital malformations such as: exstrophy-epispadias complex (exstrophy of cloaca or bladder and abnormal dorsal external genitalia; hereafter, dorsal external genitalia represents upper external genitalia); defective body wall, bladder and genitalia formation; and limb body wall defects that are probably caused by abnormalities in early development of the cloaca and urogenital sinus (Craven et al, 1997;Manner and Kluth, 2005;Penington and Hutson, 2003). The constellation of defects reported in affected individuals suggests that coordinated developmental programs regulate bladder and external genital morphogenesis.…”
Section: Introductionmentioning
confidence: 71%
“…Since the urorectal septum does not fuse with the cloacal membrane, even premature rupture of the membrane would not be responsible for imperforate anus in cloacal exstrophy. Early rupture of the cloacal membrane as the mechanism for cloacal exstrophy is also not supported by recent studies in chickens [Manner and Kluth, 2005]. Additional evidence that points to cloacal exstrophy occurring very early during organogenesis is that the omphalocele in infants with cloacal exstrophy is caudally displaced [Carey et al, 1978].…”
Section: Embryologymentioning
confidence: 96%
“…However, whether cloacal exstrophy has a different pathogenetic mechanism from bladder exstrophy remains an unresolved question. Recent data from both animal and human studies suggest that the cloacal membrane is not involved in the pathogenesis [Langer et al, 1992; Bruch et al, 1996; Nievelstein et al, 1998; Manner and Kluth, 2005] bringing that notion (i.e., cloacal membrane rupture as the mechanism) into question.…”
Section: Literature Reviewmentioning
confidence: 99%
“…exstrophy–epispadias complex) and anorectal malformations (e.g. imperforate anus; ‘persistent’ cloaca) result from abnormal development of the cloacal membrane (for reviews see Kluth & Lambrecht, 1997; Männer & Kluth, 2005). In recent years, this idea was supported by observations made in animal models which suggest that anorectal malformations might result from abnormal processes mainly affecting the caudal (anal) part of the cloacal membrane (Kluth et al.…”
Section: Discussionmentioning
confidence: 99%